Market knowledge competence – a driving force or a roadblock for radical innovations?. (1st January 2011) - Sainio, Liisa-Maija; Salojärvi, Hanna; Hurmelinna-Laukkanen, Pia; Saarenketo, Sami
There has been a debate on the role of market and customer knowledge in new product development, especially with regard to radical innovations. Although it has been stressed that market knowledge competence influences both innovative and business performance, the effects of its elements on different dimensions of innovation radicalness have not been investigated. This paper examines the radicalness of innovations from the technological, market and business perspectives. Empirical evidence in this explorative research was obtained through analysis of survey data collected among 213 companies. It was found that acquisition and dissemination of customer and competitor knowledge are accentuated in innovations with high technological radicalness, whereas, more general knowledge integration including close interaction in the marketing-R&D interface is more important in the case of high business radicalness. Contrary to other researchers, we found a higher level of knowledge acquisition and use for innovations with high market radicalness.